HJURP interaction with the condensin II complex during G1 promotes CENP-A deposition - Barnhart-Dailey, Meghan C. (Mol Biol Cell, 2017)
Centromeric chromatin is required for kinetochore assembly during mitosis and accurate chromosome segregation. A unique nucleosome containing the histone H3–specific variant CENP-A is the defining feature of centromeric chromatin. In humans, CENP-A nucleosome deposition occurs in early G1 just after mitotic exit at the time when the CENP-A deposition machinery localizes to centromeres. The mechanism by which CENP-A is deposited onto an existing, condensed chromatin template is not understood. Here we identify the selective association of the CENP-A chaperone HJURP with the condensin II complex and not condensin I. We show CAPH2 is present at centromeres during early G1 at the time when CENP-A deposition is occurring. CAPH2 localization to early G1 centromeres is dependent on HJURP. The CENP-A chaperone and assembly factor HJURP induces decondensation of a noncentromeric LacO array, and this decondensation is modulated by the condensin II complex. We show that condensin II function at the centromere is required for new CENP-A deposition in human cells. These data demonstrate that HJURP selectively recruits the condensin II chromatin-remodeling complex to facilitate CENP-A deposition in human cells.